Parent's Strategy in Formation of Student Character During Online Learning - Lailiyah, Faridatul; Sarmini, Sarmini; Harianto, Sugeng (Universitas Negeri Surabaya, 2021)
Changes in learning patterns from face-to-face to technology-based (online) cause problems, one of which is felt by parents. During the Covid-19 pandemic, parents are required to continue to carry out student character building during online learning and complete the family economy. In line with the problems that occur, the purpose of this study is to provide strategies in solving problems related to the formation of student character during online learning. This research design uses a qualitative approach with a case study method. The research was conducted on parents of UPT SMPN 6 Gresik students. The data were collected through observation and in-depth interviews and the data were analyzed using the Socialization theory of Peter L. Berger and Thomas Luckman. The results of the study indicate that the strategy referred to in this study is a series of efforts made by parents to solve problems that occur in the formation of students' character during online learning. The strategy in question includes two ways, namely external and internal. Externally, parents are expected to optimize social capital in the school environment such as teachers, principals, school residents, and the community in solving any problems including the formation of student character during online learning. Internally, parents must also be willing to be actively involved during the learning evaluation process and social control during online learning. It is important to provide reports on student progress when studying from home to teachers at school. Keywords: Parents Strategy, Character Building, Online Learning, Covid-19